Design of an IoT-Based Dam Sluice Control and Water Level Monitoring System - Efansyah, Teguh; Paramitha, Nina; Fitriani, Endah; Ariyadi, Tamsir (Universitas Nusa Putra, 2025)
The management of water resources in dams relies heavily on reliable control and monitoring systems to prevent disasters such as floods and droughts. This research aims to design and build an automatic control system for dam sluice gates and real-time water level monitoring based on the Internet of Things (IoT). This system uses ultrasonic sensors to measure water levels, microcontrollers as control centers, and servo motors to automatically adjust the sluice gate opening and closing based on a predetermined height threshold. Water level data is sent and displayed in real-time through an IoT platform so that it can be accessed by users via smartphones or computersalfariski2022automatic. The test results show that the system is able to monitor the water level with good accuracy and control the floodgates responsively according to actual conditions in the field. Thus, this system is expected to improve the efficiency of dam management and provide early information for disaster mitigation